NK Cells, Monocytes and Macrophages in HIV-1 Control: Impact of Innate Immune Responses - Mensching, Leonore; Hoelzemer, Angelique (Frontiers in Immunology, 2022)
Rapid and synchronized responses of innate immune cells are an integral part of managing viral spread in acute virus infections. In human immunodeficiency virus type 1 (HIV-1) infection, increased immune control has been associated with the expression of certain natural killer (NK) cell receptors. Further, immune activation of monocytes/macrophages and the presence of specific cytokines was linked to low levels of HIV-1 replication. In addition to the intrinsic antiviral capabilities of NK cells and monocytes/macrophages, interaction between these cell types has been shown to substantially enhance NK cell function in the context of viral infections. This review discusses the involvement of NK cells and monocytes/macrophages in the effective control of HIV-1 and highlights aspects of innate immune crosstalk in viral infections that may be of relevance to HIV-1 infection.